2013
DOI: 10.1194/jlr.m032862
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid triggers mast cell-driven atherosclerotic plaque destabilization by increasing vascular inflammation

Abstract: Atherosclerotic plaque rupture is a leading cause of acute coronary syndromes, such as unstable angina and myocardial infarction ( 1 ). Infl ammatory cells are regarded as key players in the pathogenesis of plaque rupture ( 2, 3 ), and the mast cell, a potent infl ammatory cell, has been shown to accumulate in the rupture-prone shoulder region of human atheromas ( 4 ). Activated mast cells have been identifi ed in the adventitia of vulnerable and ruptured lesions in patients with myocardial infarction, and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 38 publications
4
65
0
Order By: Relevance
“…It has been reported that LPA promotes hepatocyte secretion of apoBcontaining proteins ( 12 ) and it is possible that some of the changes noted here may be due to changes in plasma LPA levels acting on the liver. Regardless of the mechanism(s) the data presented here further add to the growing body of evidence suggesting that LPA plays a major role in lipid metabolism, infl ammation, and atherosclerosis ( 7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been reported that LPA promotes hepatocyte secretion of apoBcontaining proteins ( 12 ) and it is possible that some of the changes noted here may be due to changes in plasma LPA levels acting on the liver. Regardless of the mechanism(s) the data presented here further add to the growing body of evidence suggesting that LPA plays a major role in lipid metabolism, infl ammation, and atherosclerosis ( 7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 94%
“…The gene for lipid phosphate phosphatase 3 was identifi ed as a susceptibility locus for coronary artery disease ( 20 ). In mice, LPA was shown to trigger mast cell-driven atherosclerotic plaque destabilization ( 21 ). Thus, there is increasing evidence that LPA plays an important role in vascular pathology and atherosclerosis.…”
mentioning
confidence: 99%
“…In men with hyperlipidemia and in patients with acute cardiovascular disorders [10], plasma IgE levels were shown to be increased as well. Additional in vitro and in vivo evidence has also established a role for complement factors [11,12], neuropeptides [13,14], immune complexes [15] and lipid mediators [16] in mast cell activation during the development and progression of atherosclerosis.…”
Section: Introductionmentioning
confidence: 95%
“…Remarkably, the tissue content of unsaturated LPA in the small intestine signifi cantly correlated with the extent of aortic atherosclerosis ( 11 ). LPA is emerging as an important signaling molecule in diverse biological processes and disease states , and its role in the pathogenesis of atherosclerosis has been emphasized in recent years (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
mentioning
confidence: 99%